Analysis Of The Thought Of KH. Ahmad Dahlan And Its Implications For The Development Of Education, Akhlaq And Religion In Indonesia - Jaelani, Juhri; Alkausar, Muhammad Miftah; Nurlatifah, Nurlatifah (PT. Student Rihlah Indonesia, 2025)
In-depth religious knowledge and an incomplete understanding of education will make a person not think logically, and be apathetic. Therefore, it is very important for a person to learn a thorough understanding of religion accompanied by a balanced education. This research aims to analyze the thought of KH Ahmad Dahlan and its implications for the development of education, morality and religion in Indonesia. This research uses a qualitative approach with a literature study method. The data analysis technique uses descriptive analysis, namely collecting, processing, analyzing, and presenting data descriptively. The results of the study explain that religion and education must go hand in hand in order to achieve good akhlaq. KH. Ahmad Dahlan emphasized that Islamic education must be able to adapt to the needs of the times. Education is not only to fulfill spiritual needs but also physical, then KH. Ahmad Dahlan tried to combine religious education with general education.